Symbiotic N2 Fixation and Grain Yield of Endangered Kersting's Groundnut Landraces in Response to Soil and Plant Associated Bradyrhizobium Inoculation to Promote Ecological Resource-Use Efficiency - Mohammed, Mustapha; Jaiswal, Sanjay K.; Sowley, Elias N.K.; Ahiabor, Benjamin D. K.; Dakora, Felix D. (Frontiers in Microbiology, 2018)
Kersting's groundnut (Macrotyloma geocarpum Harms) is a neglected, endangered food and medicinal legume in Africa. Efforts to harness the benefits of the legume-rhizobia symbiosis have focused on few major legumes to the neglect of underutilized ones such as Kersting's groundnut. This study assessed plant growth, N-fixed and grain yield of five Kersting's groundnut landraces in response to inoculation with Bradyrhizobium strain CB756 at two locations in the Northern Region of Ghana. The transferability of cowpea-derived Simple Sequence Repeat (SSR) markers to Kersting's groundnut was also assessed. The symbiotic results revealed significant variation in nodulation, shoot biomass, δ15N, percent N derived from fixation, amount of N-fixed and soil N uptake. The cross-taxa SSR primers revealed monomorphic bands with sizes within the expected range in all the Kersting's groundnut landraces. The results of the aligned nucleotide sequences revealed marked genetic variability among the landraces. Kersting's groundnut was found to be a low N2-fixer, with 28–45% of its N derived from fixation at Nyankpala and 15–29% at Savelugu. Nitrogen contribution was 28–50 kg N-fixed·ha−1 at Nyankpala, and 12–32 kg N-fixed·ha−1 at Savelugu. Uninoculated plants of the Kersting's groundnut landraces Puffeun, Dowie, Sigiri and Boli, respectively, contributed 22, 16, 13, and 15 kg N-fixed·ha−1 from symbiosis at Savelugu as opposed to 89, 82, 69, and 89 kg N·ha−1 from soil. Landrace Puffeun was highly compatible with the introduced strain CB756 if based on δ15N and %Ndfa values, while Dowie, Funsi and Boli showed greater compatibility with native rhizobia in Ghanaian soils. The unimproved Kersting's groundnut in association with soil microsymbionts could produce grain yield of 1,137–1,556 kg ha−1 at Nyankpala, and 921–1,192 kg ha−1 at Savelugu. These findings suggest the need for further work to improve the efficiency of the Kersting's groundnut-rhizobia symbiosis for increased grain yield and resource-use efficiency in cropping systems.